The maturation of native uropathogenic Escherichia coli biofilms seen through a non-interventional lens - Tianqi Zhang; Sanhita Ray; Keira Melican; Agneta Richter-Dahlfors (Biofilm)
Urinary tract infections (UTI) caused by uropathogenic Escherichia coli (UPEC) are a significant global health challenge. The UPEC biofilm lifestyle is believed to play an important role in infection recurrency and treatment resistance, but our understanding of how the extracellular matrix (ECM) components curli and cellulose contribute to biofilm formation and pathogenicity is limited. Here, we study the spatial and temporal development of native UPEC biofilm using agar-based detection methods where the non-toxic, optically active fluorescent tracer EbbaBiolight 680 reports the expression and structural location of curli in real-time. An in vitro screen of the biofilm capacity of common UPEC strains reveals significant strain variability and identifies UPEC No. 12 (UPEC12) as a strong biofilm former at 28 °C and 37 °C. Non-interventional microscopy, including time-lapse and 2-photon, reveal significant horizontal and vertical heterogeneity in the UPEC12 biofilm structure. We identify region-specific expression of curli, with a shift in localization from the bottom of the flat central regions of the biofilm to the upper surface in the topographically dramatic intermediate region. When investigating if the rdar morphotype affects wettability of the biofilm surface, we found that the nano-architecture of curli guided by cellulose, rather than the rdar macrostructures, leads to increased hydrophobicity of the biofilm. By providing new insights at exceptional temporal and spatial resolution, we demonstrate how non-interventional analysis of native biofilms will facilitate the next generation of understanding into the roles of ECM components during growth of UPEC biofilms and their contribution to the pathogenesis of UTI.